1998
DOI: 10.1073/pnas.95.7.3572
|View full text |Cite
|
Sign up to set email alerts
|

Global flexibility of tertiary structure in RNA: Yeast tRNA Phe as a model system

Abstract: The study of RNA structure using x-ray crystallography or NMR has yielded a wealth of detailed structural information; however, such approaches do not generally yield quantitative information regarding long-range f lexibility in solution. To address this issue, we describe a solution-based method that is capable of characterizing the global f lexibilities of nonhelix elements in RNA, provided that such elements are f lanked by helix (e.g., bulges, internal loops, or branches). The ''phased ratio'' method is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 25 publications
2
57
1
Order By: Relevance
“…Hydrodynamic experiments indicate an overall more extended shape in the tRNA at magnesium concentrations below 100 mM (Eisinger et al 1970;Danchin and Gueron 1970;Römer et al 1970;Willick and Kay 1971;Robison and Zimmerman 1971). Quantitative measurements made by a hydrodynamic method (Friederich and Hagerman 1997;Hagerman 1997) and by gel mobility shift (Friederich et al 1998) show that above 3 mM Mg 2+ the interstem angle between the acceptor stem and anticodon stem is nearly the same as that observed in the crystal structure, but at micromolar Mg 2+ concentrations the interstem angle is z150°. Favre and coworkers (1975) used UVA irradiation (l>324 nm) of various Escherichia coli tRNAs to activate the 4-thiouridine at position 8 (s 4 U8) and showed that it specifically crosslinks to nucleotide C13.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hydrodynamic experiments indicate an overall more extended shape in the tRNA at magnesium concentrations below 100 mM (Eisinger et al 1970;Danchin and Gueron 1970;Römer et al 1970;Willick and Kay 1971;Robison and Zimmerman 1971). Quantitative measurements made by a hydrodynamic method (Friederich and Hagerman 1997;Hagerman 1997) and by gel mobility shift (Friederich et al 1998) show that above 3 mM Mg 2+ the interstem angle between the acceptor stem and anticodon stem is nearly the same as that observed in the crystal structure, but at micromolar Mg 2+ concentrations the interstem angle is z150°. Favre and coworkers (1975) used UVA irradiation (l>324 nm) of various Escherichia coli tRNAs to activate the 4-thiouridine at position 8 (s 4 U8) and showed that it specifically crosslinks to nucleotide C13.…”
Section: Introductionmentioning
confidence: 58%
“…The terminal decay time decreased to a minimum at 200 mM Mg 2+ , corresponding to an interstem angle of 70°, and increased a little as the Mg 2+ concentration was increased to 10 mM, corresponding to an angle of 80°-90°. Changes in the tRNA interstem angle and flexibility were also measured by the gel electrophoretic mobility of RNA molecules with the yeast tRNA Phe sequence (Friederich et al 1998). Mobility differences confirmed the Mg 2+ dependence of both the tRNA bend angle and the flexibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2E) and A. thaliana tRNA Val (data not shown) produced shapes reminiscent of two helices meeting at an angle, but with a more elongated conformation than that found in a highresolution tRNA Phe crystal structure (Friederich et al 1998;Shi and Moore 2000). However, application of various methods shows variability in the measured helical angles in the tRNA elbow (Friederich et al 1998). For the purposes of this study, we did not concentrate on the precise angle between these helices, but rather on how well the predicted global shape of the TLS RNAs compared with the predicted global shape of the tRNA.…”
Section: D Saxs Reconstructions Of Tlssmentioning
confidence: 83%
“…Multiple reconstructions of both yeast tRNA Phe ( Fig. 2E) and A. thaliana tRNA Val (data not shown) produced shapes reminiscent of two helices meeting at an angle, but with a more elongated conformation than that found in a highresolution tRNA Phe crystal structure (Friederich et al 1998;Shi and Moore 2000). However, application of various methods shows variability in the measured helical angles in the tRNA elbow (Friederich et al 1998).…”
Section: D Saxs Reconstructions Of Tlssmentioning
confidence: 87%